1993
DOI: 10.1016/0169-2046(93)90016-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of nature in the context of the workplace

Abstract: The well-being of the workforce is clearly a matter of concern to the employer. Such concern translates to considerable costs in the form of fringe benefit packages, health promotion programs, ergonomics, and other ways to reduce absence and enhance health and satisfaction. Despite such efforts, however, one way to address well-being that entails relatively low costs has been largely ignored in the work context. Proximity and availability of the natural environment can foster many desired outcomes, even if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
255
1
24

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(314 citation statements)
references
References 16 publications
17
255
1
24
Order By: Relevance
“…Other studies have shown that hospital patients recover more quickly and require fewer painkilling medications when they have a view of nature (Ulrich, 1984). Finally, office workers with a view of nature are more productive, report fewer illnesses, and have higher job satisfaction (Kaplan, 1993).…”
Section: Urban Forests As Economic Goodsmentioning
confidence: 99%
“…Other studies have shown that hospital patients recover more quickly and require fewer painkilling medications when they have a view of nature (Ulrich, 1984). Finally, office workers with a view of nature are more productive, report fewer illnesses, and have higher job satisfaction (Kaplan, 1993).…”
Section: Urban Forests As Economic Goodsmentioning
confidence: 99%
“…ART researchers have also begun to focus their attention on people in their everyday contexts, such as in the residential and workplace setting, where they could ordinarily and regularly find possibilities for restoration over an extended period (Kaplan 2001;Kaplan 1993). Although these studies have focused on restorative experiences supported by solely natural features, such as proximity to nearby trees and vegetation, what they do indicate is the importance of long term exposure to an everyday context, such as organization settings.…”
Section: A Rationale For the Human-nature Metaphor Of The 'Restorativmentioning
confidence: 99%
“…Connecting with nature in the workplace can reduce job stress and increase levels of job satisfaction (Kaplan, 2002). Three sub-views are discussed in matching to nature; viewing natural scenes (Cecily et al, 2005) being in natural environments (Cecily et al, 2005) and doing natural activities.…”
Section: Matching To Naturementioning
confidence: 99%